1998
DOI: 10.1103/physrevb.58.r13419
|View full text |Cite
|
Sign up to set email alerts
|

X-ray reflectivity study of temperature-dependent surface layering in liquid Hg

Abstract: We report x-ray reflectivity measurements of liquid mercury between Ϫ36°C and ϩ25°C. The surface structure can be described by a layered density profile convolved with a thermal roughness T . The layering has a spacing of 2.72 Å and an exponential decay length of 5.0 Å. Surprisingly, T is found to increase considerably faster with temperature than the ͱT behavior predicted by capillary wave theory, in contrast with previous measurements on Ga and dielectric liquids. ͓S0163-1829͑98͒52144-3͔The effect of tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
109
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 17 publications
11
109
0
Order By: Relevance
“…Recent atomic-resolution surface scattering measurements have revealed the formation of a wide variety of structures in liquid metals and alloys. Elemental Hg, Ga, and In exhibit surface-induced layering, in which atoms are stratified parallel to the liquid-vapor interface, [11][12][13][14][15] a result long predicted by theory. 16 This stratification of ions, with the corresponding oscillatory surface-normal density profile, is shown schematically in Figure 1.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Recent atomic-resolution surface scattering measurements have revealed the formation of a wide variety of structures in liquid metals and alloys. Elemental Hg, Ga, and In exhibit surface-induced layering, in which atoms are stratified parallel to the liquid-vapor interface, [11][12][13][14][15] a result long predicted by theory. 16 This stratification of ions, with the corresponding oscillatory surface-normal density profile, is shown schematically in Figure 1.…”
Section: Introductionmentioning
confidence: 89%
“…At low Au concentrations, the main effect of Au alloying is to partially disrupt the layered profile near the surface, compared to the structure of Hg. Model profiles for pure Hg at +25°C (s) and -36°C (---), calculated from eq 12 in studies reported previously, 12 are shown in Figure 7a. The oscillatory profile has a layer spacing d ) 2.72 Å, a decay parameter σ j ) 0.46 Å, and a temperature-dependent roughness σ T , given in Table 1, that determines the amplitude of the layers in the density profile.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the original prediction of Rice and coworkers that free liquid surfaces (FLS) of metals would exhibit surface layering in the density pro le (DP) perpendicular to the interface [1], (z), almost a decade had to ellapse until this expectation was realized experimentally for the case of liquid Hg [2,3], through the analysis of the x-ray re ectivity of the FLS, R(q z ), which showed a peak related to the layering. Since then, up to 2009 [4], measurements have been performed for other ve pure liquid metals, namely Ga, In, K, Sn and Bi [5].…”
mentioning
confidence: 99%